If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + 3x) = 78 (3 * 2 + 3x * 2) = 78 (6 + 6x) = 78 Solving 6 + 6x = 78 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 78 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 78 + -6 6x = 78 + -6 Combine like terms: 78 + -6 = 72 6x = 72 Divide each side by '6'. x = 12 Simplifying x = 12
| -9+6x=-3[3-2x] | | -13=m+3-8 | | 10x+20x=12x | | 4p+3=-13 | | -9=-9+x/7 | | (Z+4)and(z-6)=0 | | 5d-d-2d+8=0 | | 4y+8=2b | | 5(1-2n)-6n=37-8n | | (4w-3x)(2w+7x+5)= | | 3/4x+6=9-1/4x | | -2x+-2=4 | | 6cm+w=8cm | | d-18=8 | | 8x+10=-30 | | -3=n/10-4 | | -9v=3 | | -6=-2(h-9) | | 2(2a+2b)=10a-16b | | 4(2v+4)=-3-17 | | 4x+2(5x-1)+16=-28 | | 7x^2+53x+21=0 | | 7(y-2)=3y-34 | | 2(7x+7)=7(6x+6) | | p=4*s | | -6x-1=53 | | 18+9*3= | | -8c+4=8 | | -2-7v=-30 | | 3.5=0.5(2.5+x) | | 4(8-10)=-4-4 | | 3b-10=30 |